A cardiac hydatid cyst; four years of postoperative follow up - Gautam, Navin Chandra; Joshi, Rheecha; Aryal, Marisha; Pradhan, Rupak; Timala, Rabindra Bhakta (Nepalese Heart Journal, 2022)
Hydatid disease is a parasitic disease that mainly involves liver and lung tissues. Isolated cardiac involvement is very rare. We report a 40-year-old woman who presented in our emergency department for non-specific chest pain. She had no prior history of a hydatid disease Her transthoracic echocardiography illustrated a cystic mass in the right ventricular apex. Her contrast-enhanced computed tomographic scan of the chest showed a complex cystic lesion in the right ventricular wall at region of apex with enhancing thin wall and internal septations. Her immunological IgG test was positive for Echinococcosis. No other hydatid cysts were seen in the other organs such as liver and lungs by ultrasound scan of abdomen and computer tomography scan of chest respectively. After a week course of Albendazole, 400mg twice a day, she underwent cystectomy with cappitonage surgery under cardiopulmonary bypass. The patient was discharged from the hospital after an uneventful postoperative recovery. Echocardiographic and cardiac contrast enhanced computer tomography (CECT) evaluation in fourth year of follow-up revealed no evidence of recurrence of hydatids and ventricular function remained normal.